Scaling-up infrastructure investment to strengthen sustainable development in Brazil - Fall, Falilou (OECD Publishing, 2024)
Infrastructure investment has been low in Brazil over the last decades, leaving significant gaps in all infrastructure sectors. To close these gaps, public investment will need to increase and become more effective, while additional private resources need to be mobilised. Improving strategic planning and effectively translating it into budget allocations over time would increase the quality of infrastructure projects. Promoting foreign participation in public procurement would raise competition and value for public money, while strengthening the governance of SOEs would enhance the quality of infrastructure services. Minimising policy and judicial risks would help to leverage more private infrastructure financing, including at longer maturities, while ensuring an adequate risk sharing between public and private actors
Keywords: Economics